1995
DOI: 10.1038/377424a0
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonian-like locomotor impairment in mice lacking dopamine D2 receptors

Abstract: Dopaminergic neuronal pathways arise from mesencephalic nuclei and project axons to the striatum, cortex, limbic system and hypothalamus. Through these pathways dopamine affects many physiological functions, such as the control of coordinated movement and hormone secretion. Here we have studied the physiological involvement of the dopamine D2 receptors in dopaminergic transmission, using homologous recombination to generate D2-receptor-deficient mice. Absence of D2 receptors leads to animals that are akinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

50
387
5
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 600 publications
(443 citation statements)
references
References 27 publications
50
387
5
1
Order By: Relevance
“…The generation of mice lacking D2 receptors has been reported previously (Baik et al 1995). The intrinsic and synaptic membrane properties of neurons recorded in vitro from D2 lacking striatal slices were similar to those recorded from wild-type mice and control rats, as previously reported (Calabresi et al 1997).…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…The generation of mice lacking D2 receptors has been reported previously (Baik et al 1995). The intrinsic and synaptic membrane properties of neurons recorded in vitro from D2 lacking striatal slices were similar to those recorded from wild-type mice and control rats, as previously reported (Calabresi et al 1997).…”
Section: Methodssupporting
confidence: 78%
“…In some cases, 6-OHDAlesioned rats were anaesthetized with diethyl ether and brain dissection confirmed that the nigrostriatal pathway was lesioned. This was monitored by using a monoclonal antibody for tyrosine-hydroxylase.The generation of mice lacking D2 receptors has been reported previously (Baik et al 1995). The intrinsic and synaptic membrane properties of neurons recorded in vitro from D2 lacking striatal slices were similar to those recorded from wild-type mice and control rats, as previously reported (Calabresi et al 1997).…”
supporting
confidence: 78%
“…We and others have observed that D 2 KO mice exhibit significantly less locomotor activity than WT controls (Figures 2b and e) (Baik et al, 1995;Kelly et al, 1998;Phillips et al, 1998). D 2 KO mice also had a tendency to exhibit more circumscribed movements (increased spatial d; Figure 3).…”
Section: Discussionmentioning
confidence: 64%
“…Most experiments were performed with D2R À / À mice (B6;129S2-Drd2tmllow) obtained from the Induced Mutant Resource at the Jackson Laboratory (Bar Harbor, ME), as described previously [18][19][20] . The D2R À / À mice and WT littermates used in the initial phase of the study originated from the breeding of D2R þ /-heterozygotes, as described previously 14 . Mice were maintained in a specific pathogen-free barrier facility under constant conditions of temperature and humidity, and on a 12-h light, 12-h dark schedule.…”
Section: Methodsmentioning
confidence: 99%
“…Dopamine receptors are members of the G protein-coupled receptor family and are classified into D1-like receptors (D1 and D5) and D2-like receptors (D2, D3 and D4). The dopamine D2 receptor (D2R) is highly expressed in the central nervous system and has an important role in the regulation of diverse neural functions by dopamine [14][15][16][17][18][19][20] . It has been shown to act as an autoreceptor in presynaptic regions of the substantia nigra and ventral tegmental area in the midbrain 21 , suggesting that it may have an important role in the central regulation of homeostasis of dopaminergic neurotransmission 18,19,21 by acting at both the postsynaptic and presynaptic levels.…”
mentioning
confidence: 99%